Error calibration of quasi-geoidal, normal and ellipsoidal heights of Sweden using variance component estimation - ESHAGH, Mehdi (Contributions to Geophysics and Geodesy, 2010)
Errors of estimated parameters in an adjustment process should be scaledaccording to the size of the estimated residuals or misclosures. After computing a quasigeoid(geoid), its biases and tilts, due to existence of systematic errors in the terrestrialdata, are removed by fitting a corrective surface to the misclosures of the differencesbetween the GNSS/levelling data and the quasi-geoid (geoid). Variance component estimationcan be used to re-scale or calibrate the error of the GNSS/levelling data and thequasi-geoid (geoid) model. This paper uses this method to calibrate the errors of the recentquasi-geoid model, the GNSS and the normal heights of Sweden. Different stochasticmodels are investigated in this study and based on a 7-parameter corrective surface modeland a three-variance component stochastic model, the calibrated error of the quasi-geoidand the normal heights are 6 mm and 5 mm, respectively and the re-scaled error of theGNSS heights is 18 mm.